URGENSI PELAKSANAAN PENDAFTARAN TANAH ADAT DI PROVINSI JAMBI - Herlina Manik; Suhermi Suhermi; Pahlefi Pahlefi (Ensiklopedia of Journal, 2022)
Land is a vital component of human life and has economic worth. According to a Javanese adage, "sedhunuk bathuk senyarii bumi" signifies that one inch of land will be preserved even at the cost of one's life. The lack of legal protection for indigenous people's land has resulted in a plethora of land conflicts with parties with legal standing. Indigenous people have had a difficult time protecting their land against parties with legal protection due to the lack of formal and legitimate land ownership proof. Formal and authentic evidence of property ownership is critical in preventing land dispute. Indigenous peoples must register their lands in order to obtain authentic and formal evidence of their ownership. The purpose of this research is to determine the urgency of registering customary lands, as well as the primary cause for registering the communal lands. Additionally, this study will investigate the procedure of registering customary lands. This research included empirical methodologies, which included data collection, data processing, and data analysis. The outcome will be presented in a systematic and objective manner to assist in the resolution of a problem or the testing of a hypothesis. Land tenure, land registration, and land rights are all terms that refer to customary land.